Numerical investigation of unstable rock failure in underground mining condition. (January 2015) - Gu, R.; Ozbay, U.
Abstract: Underground coal mining affects the stress distribution in rock mass and may induce slip failures along large existing rock discontinuities and sizable compressive failures of coal in mining faces and sidewalls. When such failures occur in an unstable and uncontrollable manner, they can be accompanied by a significant release of strain energy from the surrounding rock and potentially create coal burst events. This paper focuses on identifying failure stability of rock and rock discontinuities in terms of their manifestation as stable and unstable manner in coal mining settings. The studies use numerical modeling and consider failure stability of both rock discontinuities in slip and coal material in compression. The influence of the slip failure stability on the compressive failure stability is also investigated. The Universal Distinct Element Code (UDEC) is used with its optional constitutive models the Continuously Yielding joint and the Mohr–Coulomb strain softening model. A laboratory scale numerical model of a double shear test setup is developed and used to assess the ability of the numerical code in detecting the stability during discontinuity slip failures. The studies performed using this model confirmed the ability of the numerical code in differentiating stable and unstable slip failures when using the failure stability criterion based on the relative stiffnesses of loading system and failing discontinuities. Using the numerical double shear test models, criteria and tools are developed for identifying the failure stabilities in larger in situ scale numerical models. The in situ scale models allowed studies of the failure stabilities of existing rock discontinuities under the influence of an advancing excavation. The results show that both stable and unstable slip failures can occur at an existing rock discontinuity depending on the post-failure characteristic of the discontinuity and the loading stiffness of the surrounding rock. The loading stiffness is observed to continuously reduce with increasing mining extent. Additional in situ models are also built to study the effect of coal seam–host rock interfaces on the failure stability of sidewalls and mining faces in coal mining settings. The results show that unstable sidewall failures may occur when a sudden de-confinement is triggered by an unstable slip failure at the coal–rock interfaces. The existence of weak regions along such interfaces can also contribute to unstable compressive failures of mining faces and sidewalls.